A Five-Year financial plan for LBC Express, Inc. - Agustin, Lois Clarisse F., Calanoc, Kent C., De Guzman, Clarriza Maie D., Esporlas, John Kenneth T., Gatus, Gerylle Guia O., Junatas, Jeremy Joe H., Prades, Redelyn A. 4 0 16; 5
EXECUTIVE SUMMARY: LBC Express, Inc., a leading logistics and courier provider in the Philippines, is facing significant financial challenges despite its strong market presence. The company is experiencing high levels of trade and other receivables, reliance on loans, and elevated interest expenses, all of which are adversely affecting its liquidity and profitability. These financial constraints threaten the company's long-term sustainability and hinder its ability to fund operations and strategic investments. The objective of this financial plan is to address the issues related to receivables management by improving liquidity and reducing financial costs. The plan includes an analysis of LBCE's financial performance, identifying key problems such as slow collections and excessive borrowings. The specific goals are to enhance receivables collection, decrease accounts payable, and improve cash reserves. A comparative financial analysis was conducted, using performance ratios and financial statements to benchmark LBCE's position against competitors. Key statistical tools such as financial ratio analysis, market share, and trend forecasting were utilized to gain insights into the company's financial health and operational efficiency. Several alternative courses of action were considered, including outsourcing credit agencies to enhance receivables collection, integrating accounting software for more efficient processes, and implementing a moderate credit policy. The analysis revealed that a moderate credit policy could effectively mitigate the receivables issue, reduce the company's dependency on borrowings, and enhance liquidity. A recommendation to implement this policy is presented, which involves a modest investment of P380,000 and promises significant returns, including a 40% reduction in receivables, a 40% increase in cash reserves, a 12% reduction in payables, and a 45% decrease in interest expenses. Although challenges like potential revenue loss and customer friction may arise from stricter credit terms, these risks can be managed through effective communication and customer relationship management. The proposed solution will improve operational efficiency, reduce financial risks, and position LBC for sustainable growth in the competitive logistics sector.
Financial Plan: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2